Pendampingan Pencatatan Keuangan Berbasis Aplikasi untuk Meningkatkan Keterampilan digitalisasi UMKM Toko Seragam Sekolah - Hari Sriwijayanti; Shinta Bella; Nike Apriyanti (ARDHI : Jurnal Pengabdian Dalam Negri, 2026)
This activity aimed to improve the digitalization knowledge and skills of Toko Seragam Sekolah Empat Bersaudara, an MSME located in Pasar Raya Padang, through application-based financial recording assistance. The methodology applied a participatory approach based on partner needs through preparation, socialization, training, technology implementation, mentoring, evaluation, and program sustainability stages. The activity focused on practical use of BukuWarung and BukuKas applications to record sales, purchases, operational expenses, inventory data, and simple financial reports. The results showed an improvement in the partner’s understanding of structured financial recording, separation of business and personal finances, and the use of financial reports as a basis for business decision-making. The partner also began to independently input transactions, manage inventory, read automatic reports, and use financial data to control cash flow, profit and loss, and inventory needs. The implication of this activity indicates that practical application-based assistance can be an effective strategy to strengthen MSME digital financial literacy and encourage more orderly, accurate, efficient, and sustainable business management.